Response Analysis of Deceleration Motion Control for Pipeline Intelligent Plugging Robot - Wang Shanshan; Jiang Zhengguo (Shiyou jixie, 2025)
Pipeline intelligent plugging robot （PIPR） is an indispensable high-end equipment for rapid maintenance and emergency repair operation of pipeline within 12 hours. Achieving efficient and stable deceleration is crucial to the success of plugging operation. A hydraulic control system was designed for a PIPR that uses friction between the slip and the pipe wall to achieve deceleration and positioning. Then， a nonlinear dynamic model of constant deceleration was built for the servo PIPR based on fuzzy PID control. Finally， the numerical simulation method was used to conduct a mechanical-hydraulic co-simulation of the hydraulic control system， and study the influence of important parameters of the control system on the dynamic control stability of the PIPR during the deceleration process. The study results show that as the initial velocity increases， the centroid acceleration of the PIPR gradually increases， with a maximum overshoot of -3.4 m/s2， deceleration process control time within 30 seconds， and positioning accuracy within 5%. Increasing the expected deceleration distance can effectively reduce positioning error； the capacity of the accumulator should be at least greater than 0.25 L. The number of accumulators has a relatively small impact on the system.